2012
DOI: 10.1002/jor.22183
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral blood mononuclear cells enhance the anabolic effects of platelet‐rich plasma on anterior cruciate ligament fibroblasts

Abstract: Use of platelet-rich plasma (PRP) has shown promise in various orthopaedic applications, including treatment of anterior cruciate ligament (ACL) injuries. However, various components of blood, including peripheral blood mononuclear cells (PBMCs), are removed in the process of making PRP. It is yet unknown whether these PBMCs have a positive or negative effect on fibroblast behavior. To begin to define the effect of PBMCs on ACL fibroblasts, ACL fibroblasts were cultured on three-dimensional collagen scaffolds … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
49
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 48 publications
(54 citation statements)
references
References 35 publications
2
49
0
Order By: Relevance
“…L‐PRP promoted a higher expression of MMPs , which are activated trough the NF‐kB p65 pathway induced by IL6 . MMPs play an essential role in remodeling of soft tissue although when over‐expressed a catabolic environment is created . In line with our results McCarrel et al showed, that 2.5% L‐PRP concentration stimulated MMP3 , whereas 20% L‐PRP promoted MMP13 expression.…”
Section: Discussionsupporting
confidence: 92%
“…L‐PRP promoted a higher expression of MMPs , which are activated trough the NF‐kB p65 pathway induced by IL6 . MMPs play an essential role in remodeling of soft tissue although when over‐expressed a catabolic environment is created . In line with our results McCarrel et al showed, that 2.5% L‐PRP concentration stimulated MMP3 , whereas 20% L‐PRP promoted MMP13 expression.…”
Section: Discussionsupporting
confidence: 92%
“…Autologous blood is added to an extracellular matrix scaffold and held in place in the fluid environment of the knee, where the cells in the blood stimulate ligament healing. 10,11,28,37 Thus, the BEAR technique is designed for tears in which the 2 ends of the torn ligament cannot be reapproximated under compression. In this study, only 2 of the 242 screened patients were thought to have insufficient tissue on their preoperative MRI for the BEAR procedure, and no patients were found at surgery to have insufficient tissue (<50%) for the BEAR technique.…”
Section: Discussionmentioning
confidence: 99%
“…Plateletrich plasma is a simple preparation of a complex material, and as such may be viewed as a potential platform for further development of regenerative strategies. For example, a recent study found that the effects of platelet-rich plasma on collagen production by ligament fibroblasts could be enhanced by the simultaneous presence of autologous peripheral blood mononuclear cells, suggesting a potential direction for modification of therapy [43].…”
Section: Regenerative Injection Therapy (Prolo-therapy) For Musculoskmentioning
confidence: 99%